Estudo do balanço nitrogenado e da digestibilidade da matéria seca e proteína de rações, para ovinos, suplementadas com amiréia, uréia ou farelo de algodão - Salman, AKD; Matarazzo, S. V.; Ezequiel, JMB; Kronka, S. N.; Seixas, JRC; Soares, WVB; Martins, A. P. (Revista Sociedade Brasileira Zootecnia, 1997)
To evaluate the nutritional value of rations supplemented with different protein sources, an in vivo digestibility trial was conducted to determine the coefficients of digestibility for dry matter (DMDC) and crude protein (CPDC), nitrogen balance (NB) and the fecal non-protein nitrogen (NPN). Twenty - four 11-months - old lambs weighing 30.4 +/- 3.0 kg were blocked on the basis of their body weight and randomly allocated to three treatments groups; suplemented with cottonseed meal (CSM), starea (ST) or urea (UR). The DMDC was statistically superior for the Starea treatment (67.7%) over the others (64.3% and 64.1% for CSM and UR). The CSM, UR and ST rations had no influence on CPDC (63.9; 66.9 and 69.4%, respectively) and on fecal NPN (1,3; 1,2 e 1,3 g/day, respectively). The NB results were similar also among treatments (13,4; 9,0 e 10,5 g/day to CSM, UR and ST, respectively) although the ST treatment lambs excreted larger amounts of nitrogen in the urine (7.7 g/day) in relation to CSM (4.8g/day) and similar to UR treatment (6.5 g/day). Starea supplement in ruminant diets increased dry matter digestibility when compared to cottonseed meal and urea, but did not improve the efficiency of the nitrogen utilization by lambs.
Study of the nitrogen balance and dry matter and protein digestibility of rations, for lambs, supplemented with Starea, urea or cottonseed meal
Keywords: starea; Nitrogen balance; Digestibility; cottonseed meal; Lambs; urea